Decentralisation and Poverty Reduction: A Conceptual Framework for the Economic Impact - Susan Steiner (German Institute of Global and Area Studies (GIGA), 2005)
This paper contributes to providing insights into the impact of decentralisation on poverty. It starts out with an overview of which role decentralisation plays in strategies and policies for poverty eradication and derives economic and political impact channels. It concentrates on the economic channel, the reasoning of which is rooted in fiscal federalism theory. It shows that decentralisation cannot only influence poverty by assigning expenditure responsibility to lower levels of government but also by assigning tax-raising power, which has so far been neglected by the literature. The paper concludes by pointing out a number of possible risks for realising the poverty-reducing potential of decentralisation.
Keywords: I38; H72; H71; 330; Local public goods; local revenue; poverty; Dezentralisierung; Armutsbekämpfung; Finanzbeziehungen; Gemeindesteuer; Lokale öffentliche Güter; Armut